2017
DOI: 10.3389/fimmu.2017.01700
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Killer Cell Activity and Interleukin-12 in Metabolically Healthy versus Metabolically Unhealthy Overweight Individuals

Abstract: The purpose of this study was to determine whether the immune system is involved in the different metabolic circumstances in healthy and unhealthy overweight individuals. We examined the metabolic and immune characteristics of 117 overweight individuals. Subjects were classified as metabolically healthy overweight (MHO, n = 72) or metabolically unhealthy overweight (MUO, n = 45). The immune response was measured by circulating levels of natural killer (NK) cell activity and cytokines. Both groups were comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Similar to our results, some studies have reported a relationship between unhealthy metabolic status and reduced NK cell activity. 10 11 12 Kim, et al 10 showed that a metabolically unhealthy overweight group (higher BP and higher serum levels of triglyceride, glucose, glucose-related markers, and lower levels of HDL-C) had lower NK cell activity than a metabolically healthy overweight group. Lynch, et al 11 also reported that healthy obese patients had higher levels of NK cells, compared with unhealthy obese patients, and had similar NK cell levels to lean healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, some studies have reported a relationship between unhealthy metabolic status and reduced NK cell activity. 10 11 12 Kim, et al 10 showed that a metabolically unhealthy overweight group (higher BP and higher serum levels of triglyceride, glucose, glucose-related markers, and lower levels of HDL-C) had lower NK cell activity than a metabolically healthy overweight group. Lynch, et al 11 also reported that healthy obese patients had higher levels of NK cells, compared with unhealthy obese patients, and had similar NK cell levels to lean healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some researchers have shown decreased NK cell activity in metabolically unhealthy, obese individuals, and suggested that the immune system is involved in the different metabolic statuses of healthy and unhealthy obese individuals. 10 11 12 However, previous studies on this topic also employed small sample sizes, and the link between different metabolic phenotypes and immunity still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 induces the expression of cytotoxic mediators and increased production of cytokines, especially IFN-γ, in NK cells, T cells, and natural killer T cells. The study of Kim et al [36], suggested that IL-12 levels in addition to NK cell activity could be better indicators for predicting individuals who are at early immune risk than serum levels of TNF-α, IL-6 and IL-1β. Along with our results, the study of obesity in the Mexican adult population revealed that, overweight and subjects with obesity (21 women with BMI ≥ 30 kg/m 2 ) had higher levels of IL-12 than a normal-weight group.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of the lipid panel, free fatty acids, a glucose-related panel, serum gamma-glutamyltransferase (gamma-GT) assayed via a modified Sanz method, and serum high-sensitivity C-reactive protein (hs-CRP) assayed via a latex-agglutination turbidimetric immunoassay were measured by a Hitachi 7600 autoanalyzer (Hitachi, Tokyo, Japan). Plasma adiponectin concentrations were measured by an enzyme immunoassay [ 11 ], and leptin was measured with a Human Leptin ELISA kit (Millipore, Darmstadt, Germany) by SpectraMax190 (Molecular Devices, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%